Challenges and Opportunities for Women Entrepreneurs in the 21st Century in Bangladesh:: Examining the Impact of Entrepreneurship Education - Chowdhuri, Abu Sayef Md. Muntaquimul Bari; Hossain, Md. Shahadat; Saha, Goutam; Das, Mridul Kanti (Jahangirnagar University Journal of Management Research, 2024)
The objective of this study is to look at the challenges and opportunities that women business owners in Bangladesh confront, as well as how entrepreneurship education might help them learn how to run a profitable business. With the use of a stratified random sampling technique, researchers were able to reach 300 female entrepreneurs from large cities and towns, representing a wide range of ages, educational backgrounds, occupations, and geographic areas. To gather information, a semi-structured questionnaire was utilized. Women entrepreneurs faced numerous obstacles, including limited access to capital, insufficient training resulting in a deficit of technical knowledge, being unfamiliar with funding and technical support resources, intense market competition, unfulfilled needs for acceptance and support, and a lack of comprehension regarding marketing strategies. Applying a mixed-methods strategy to delve further into the participants’ experiences might have potentially yielded more fruitful results. Women business owners located in the Dhaka, Chittagong, Sylhet, Khulna and Rangpur areas were the only ones included in the survey. Maybe some rural women business owners might have listened if it had been there. These restrictions will be scope for further research. The study’s practical implications include the following: increased training for women entrepreneurs is necessary so they can acquire more knowledge and skills; if financial institutions were more welcoming to women entrepreneurs, it would empower these individuals whose businesses show promise; and the development of more pro-women entrepreneurship policies would boost the activities of women entrepreneurs. When empowered, women may achieve equal success in the corporate world as males.